Determinar el nivel de reabsorción radicular externa posterior al tratamiento ortodóntico realizado en un Centro Especialista en Ortodoncia de la ciudad de Loja - Enríquez Gualán, Walter Iván (2019)
The present study is analytical, observational, and retrospective. The objective was to determine whether or not there was a degree of external root reabsorption after having an orthodontic treatment, as well as knowing the entire process of root reabsorption, from its etiology, etiopathogenesis, classification, evaluation and the factors that are associated with this pathology in order to prevent it, avoid it or treat it. The study population consisted of 30 people, 15 men and 15 women, giving as a final result a sample of 60 radiographs used 30 initial and 30 final radiographs. To determine the degree of external root reabsorption panoramic radiographs of the patients who went to the orthodontic specialist center in the period 2011-2018 were used, performing the respective traces of the initial radiographs and their respective control radiographs, in the engineer paper. After verifying the correct outline by the teacher, all the dental pieces were measured in millimeters, both of the initial radiographs, as of the finals, after this, it was compared if it existed or not of differences in the length of the teeth before treatment and once the orthodontic treatment was finished, determining thus, if it existed or not, an external root reabsorption. The results obtained from this analysis helped to conclude that 81.76% of the pieces suffered reabsorption and grades 1, 2 and 3 were the most frequent. Grade 4 was detected in only two pieces. There was no reabsorption (grade 0) in 18.24% of the pieces (n = 135). In addition, it was determined that the degrees of reabsorption between the upper pieces with respect to the lower pieces were in different proportions. The differences was significant. Key words: Root reabsorption, pathology, orthodontics.